Phage resistance mutation triggered by OmpC deficiency in Klebsiella pneumoniae induced limited fitness costs. (June 2022) - Cai, Ruopeng; Deng, Hewen; Song, Jinming; Zhang, Lei; Zhao, Rihong; Guo, Zhimin; Zhang, Xinxin; Zhang, Hao; Tian, Tian; Ji, Yalu; Shi, Kun; Li, Jianming; et al.
Abstract: Outer membrane proteins (OMPs) play an important role in bacterial fitness costs. Derived from the interaction between Klebsiella pneumoniae K7 and phage GH-K3, K7R B is an outer membrane porin-deficient phage-resistant mutant strain triggered by ompC 712 deletion, exhibits expression inhibition of OmpC, OmpN, KPN_02430 and OmpF, but its fitness costs and regulatory mechanism remains unknown. In this study, compared with K7, K7R B showed almost unaffected growth rate, slightly decreased virulence, and increased resistance to some antibiotics. Transcriptome analysis showed that the pathways of glycerolipid metabolism and nitrogen metabolism in K7R B were significantly inhibited, while the transcription of permeases belonging to ABC transporters tended to be active, nutrient uptakes such as citrate and phenylalanine were also enhanced. However, transcriptional up-regulation in K7R B was inhibited by overexpression of OmpC, OmpN, KPN_02430 and OmpF in general. Overexpression of OmpN, KPN_02430 and OmpF, respectively, restoring the sensitivity of strains to antibiotics to varying degrees, while OmpC overexpression aggravated the bacterial drug-resistance especially to β-lactam antibiotics. Besides, unlike OmpC and OmpF, overexpression of OmpN and KPN_02430 reduced bacterial virulence. In brief, by revealing the limited fitness costs of phage-resistant mutant K. pneumoniae with porin-deficiency, our study providing a reference for the design and development of drugs to inhibit the ways of bacterial metabolic rewiring and to increase fitness costs. Highlights: Phage resistance mutation of K. pneumoniae K7R B comes at a limited fitness cost. K7R B is accompanied by dramatic alterations in metabolic gene transcription. Four porins–OmpC, OmpN, KPN_02430 and OmpF regulate the fitness of K7R B .